(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Refractive errors, particularly myopic astigmatism, significantly affect visual function and quality of life (QoL). LASIK surgery has become a popular corrective option, offering spectacle independence and rapid visual recovery. However, comparative evidence on patient-reported outcomes between femtosecond laser-assisted and mechanical microkeratome-assisted LASIK remains limited. This study aims to evaluate the impact of LASIK on QoL using the validated Quality-of-Life Impact of Refractive Correction (QIRC) questionnaire and to compare outcomes across surgical techniques and nonsurgical correction methods. Material and methods: This prospective observational study included 150 patients with myopic astigmatism, aged 20–50 years, divided into three groups: femtosecond LASIK (n = 50), microkeratome LASIK (n = 50), and spectacle/contact lens users as controls (n = 50). The QIRC questionnaire was administered preoperatively and at one-month postoperatively for LASIK groups, and once for the control group. QIRC scores were analyzed for total, functional (Q1–Q13), and emotional (Q14–Q20) domains. Statistical comparisons were conducted using paired and independent t-tests, ANOVA, and effect size estimates. A clinically meaningful QoL improvement was defined as a ≥10-point increase in total QIRC score. Results: Both LASIK groups demonstrated statistically and clinically significant improvements in total QIRC scores (femtosecond: +14.20 ± 5.3; microkeratome: +12.37 ± 4.8; p < 0.001). Postoperative scores in LASIK patients were significantly higher than those in the control group (p < 0.001). No statistically significant difference was observed between the two surgical techniques in postoperative QoL (p = 0.7865). Subscale analysis showed significant improvements in both functional and emotional domains, with females reporting greater gains in emotional well-being. No intraoperative or postoperative complications were recorded. Conclusion: LASIK significantly enhances quality of life in patients with myopic astigmatism, with comparable outcomes between femtosecond laser and mechanical microkeratome techniques. The QIRC questionnaire proved effective in quantifying patient-perceived benefits, supporting its use in routine refractive surgery assessment. Integration of PROMs into clinical practice can facilitate more holistic and personalized patient care.